Development and characterization of innovative carbon-based waste ashes/epoxy composites. (2021) - Stasi, Enrica; Giuri, Antonella; La Villetta, Maurizio; Cirillo, Domenico; Guerra, Gaetano; Maffezzoli, Alfonso; Ferraris, Eleonora; Esposito Corcione, Carola
Abstract: In this study, carbon based ashes were produced by the wooden biomass pyro-gasification plant CMD ECO20. CMD ECO20 is a micro-scale combined heat and power system powered with biomass, under development by the Italian company Costruzioni Motori Diesel (C.M.D) S.p.A. It is an integrated system combining a downdraft gasifier, a spark ignition internal combustion engine, an electric generator and syngas cleaning devices, and it is able to produce electric and thermal power up to 20 kWe and 40 kWth. Three different types of fillers were produced from ashes starting from innovative green waste: the first type (MA) was obtained by mortar milling, while the second (DBA) and the third (WBA) one were produced by dry and wet ball milling, respectively. MA, DBA e WBA fillers were characterized by several techniques including Scanning Electron Microscopy (SEM), Multi-angle light scattering (MALS) and Energy Dispersive X-ray (EDX) Spectrometry. Each filler was added to epoxy resin EC01 in an amount equal to 1, 3, 5 and 10 wt%. The curing agent (22phr) was added to the resin that was cured for 1 h at 60 °C and 2 h at 150 °C. Finally, the flexural properties and the glass transition temperature of the cured neat epoxy and ashes filled epoxy composites were measured. The elastic modulus of the epoxy resin containing an amount of fillers from 1 to 10 wt% is higher in comparison to that of the neat epoxy. The flexural strength of the epoxy resin containing an amount of DBA of 3 wt% is also higher than that of the neat epoxy.